Increased vulnerability of clinical research units during the COVID‐19 crisis and their protection. Issue 17 (2nd June 2020) - de Miguel, Maria; Doger, Bernard; Boni, Valentina; Hernández‐Guerrero, Tatiana; Moreno, Irene; Morillo, Daniel; Moreno, Victor; Calvo, Emiliano
Abstract : Lay Summary: Currently, the complexity of clinical trial development in oncology is being further complicated by the coronavirus disease 2019 (COVID‐19) pandemic, which is reducing the resources needed to comply with protocol‐specific procedures while putting patients in units, who are already vulnerable, at increased general risk not only for COVID‐19 infection but also with respect to their baseline disease. Individualizing the management of patients while ensuring their safety and adherence to the study protocol, establishing specific staff contingency plans, and maintaining sponsor and contract research organization (CRO) alignment are some of the key issues for maintaining the continuity of cancer patients' investigational treatment and minimizing their infection risk as well as the risk to staff members of the unit, sponsors, and CROs while maintaining the integrity of data quality and compliance with good clinical practice. Abstract : This commentary describes the potentially deep, specific, and rapid impact of the coronavirus disease 2019 pandemic on clinical research units in oncology, and it establishes different processes and action plans in order to allow the performance of clinical research activities during this challenging period.